Polite ignorance - Cvetanoska, Hristina (Amfiteater (Ljubljana), 2018)
The article analyses Slovenian-Macedonian exchange in the field of drama, which seems to be a moderate one. In the period from 1990 till 2015, there were six Macedonian texts staged in Slovenian institutions and eight Slovenian ones in Macedonian theatres. Furthermore, contemporary Slovenian authors are completely absent from Macedonian theatre life and Macedonian ones are represented with three names only. Though it might seem to be a natural decline after the fall of Communism and the disintegration of former Yugoslavia, this seems to be only partly the case.
Keywords: Aleksandar Popovski; Dane Zajc; Drago Jančar; Dušan Jovanović; Goran Stefanovski; Macedonian drama; makedonska drama; Slovenian drama; Slovenian-Macedonian theatre exchange; slovenska drama; slovensko-makedonske izmenjave